2003
DOI: 10.1007/s10295-003-0040-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of cloning vectors and transformation methods for Amycolatopsis

Abstract: The genus Amycolatopsis is of industrial importance, as its species are known to produce commercial antibiotics. It belongs to the family Pseudonocardiaceae and has an eventful taxonomic history. Initially strains were identified as Streptomyces, then later as Nocardia. However, based on biochemical, morphological and molecular features, the genus Amycolatopsis, containing seventeen species, was created. The development of molecular genetic techniques for this group has been slow. The scarcity of molecular gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 54 publications
(100 reference statements)
0
17
0
Order By: Relevance
“…Previous studies done with Amycolatopsis sp. ATCC 39116 and with members of the genus Amycolatopsis in general have shown that it is quite difficult to generate deletion mutants (5,6,38). Therefore, our first goal was to improve the homologous integration of the generated suicide plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies done with Amycolatopsis sp. ATCC 39116 and with members of the genus Amycolatopsis in general have shown that it is quite difficult to generate deletion mutants (5,6,38). Therefore, our first goal was to improve the homologous integration of the generated suicide plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…The Amycolatopsis strains have often proven difficult to transform and genetically manipulate (Malhotra & Lal, 2007;Dhingra et al, 2003). We have invested very significant efforts to develop a transformation procedure for A. sulphurea, where we tested various growth media, numerous actinomycete plasmids (replicative and integrative) in combination with different procedures, such as protoplast transformation and E. coli-A.…”
Section: Resultsmentioning
confidence: 99%
“…However, with the availability of rifamycin polyketide synthase gene cluster (rifPKS) in 1998 [12] (Fig. 3) and with the development of cloning vectors and transformation system for the rifamycin producer strain A. mediterranei by our group here at the University of Delhi [13][14][15][16][17][18], the possibilities of manipulating the rifPKS to produce more effective analogues of rifamycin B were raised [16].…”
Section: Modification Of Rifamycin Polyketide Backbone: Generating Rimentioning
confidence: 99%
“…The prerequisites for the generation of rifamycin analogues involved developing a cloning vector and transformation system to negotiate with the bacterium A. mediterranei that produces Rifamycin B. Thus, a work initiated in 1988 resulted in crossing the first hurdle by developing a system of cloning vectors and transformation system by our team [13,15,18].…”
Section: Stepping Stones For Generation Of 24-desmethylrifampicinmentioning
confidence: 99%